(untitled) (Educação em Revista, 2022)
The present study aimed to establish, from the generating themes, thematic networks that would enable the transversal organization of financial education in the curriculum of the technical course in information technology integrated with high school education at Campus Sena Madureira, at the Federal Institute of Acre (IFAC). In order to obtain the generating themes and to constitute the thematic network, the methodological procedures of the Freirian thematic approach dynamics were adopted. The breadth of disciplinary involvement denoted that there were traces of harmonic correlation between the generating themes and financial education as a transversal school thematic axis, which expanded the possibility of offering financial education under dialogical, problematizing, and critical-transforming perspectives. From the investigation of the generative themes, a thematic network was organized that made possible the transversal insertion of financial education in the integrated high school curriculum, configuring itself under a critical-reflective perspective, from the perspective of multidisciplinary and transversal teaching. The contents proposed by the thematic reduction offered a potential and important contribution to the elaboration and implementation of integrative projects, as these are articulators of different fields of knowledge. Finally, the dynamics of Freire’s thematic approach were validated as an appropriate method for the transversal insertion of financial education from a critical-transforming perspective, from which it becomes possible to carry out school education based on omnilateral, unitary, and polytechnics.